The effects of COVID-19-related stress among parents and children in Ohio child care programs: a mixed-methods study. Issue 4 (2nd October 2022) - Burkhart, Kimberly; Minnes, Sonia; Yamoah, Owusua; Doernberg, Ellen; Balser, Sarah; Ciesielski, Timothy; Dimitropoulos, Anastasia; Nock, Nora L.; Freedman, Darcy A.
ABSTRACT: COVID-19-related stress effects on the caregiver and child are largely unexplored. Caregivers (N = 114) of children between the ages of 3 months and 10 years accessing Ohio child care completed a parent survey (fall 2020), and additional caregivers (N = 20) completed an interview. Caregivers reported a mean of 70 (SD = 19; scale 1–100) on COVID-19-related stress. In adjusted regression models, higher caregiver-reported COVID-19-related stress was associated with increased odds of child aggression and poor social skills. Exploratory analyses indicated that these associations may be partly mediated by the caregiver working from home and losing their temper. Qualitative findings reflect caregiver COVID-19 stress and complement quantitative findings. Caregivers and children who experience COVID-19 stress should be monitored for persistent problems.